Association between Asthma in Children and Mode of Delivery - E Mohammadzadeh,; E Babazadeh; R Alizadeh Navaei (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Bābul, 2009)
BACKGROUND AND OBJECTIVE: Asthma is one of the most frequent chronic respiratory diseases and relation between caesarean and asthma is controversy. Regarding high number of caesarean in this area, the aim of this study was to determine the relation between asthma and mode of delivery in the asthmatic children compared with the control group.METHODS: This case-control study performed on 512 children in case and control groups that were between 3 to 14 years. Case group included children with asthma and control group included children without asthma that referred to Amirkola hospital. Case and control were matched by age. The collected information for both group contained: mode of delivery, demographic variables and effective factor for asthma.FINDINGS: There was cesarean in 159 subjects (62.1%) of case group and 147 subjects (57.4%) (OR=1.2, CI95%: 0.8-1.7) that showed no significant difference. Distribution of sex, passive smoking, gestational age, hospitalization due to severe respiratory infection in first year that there was no significant difference between case and control groups but contact to pets in control and family history of asthma in case group were significantly higher (p<0.05). CONCLUSION: The results of present study show that there was no relation between mode of delivery and asthma in children.